International Approaches to the Development, Validation, and Change Management of Analytical Procedures (Review) - A. V. Fetisova; Zh. I. Aladysheva; N. V. Pyatigorskaya; O. A. Zyryanov; M. M. Marshalova (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. In 2023, the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) published a new Guideline on Analytical Procedure Development (ICH Q14) and a revised version of the Guideline on Validation of Analytical Procedures (ICH Q2(R2)). Consequently, there is a need for a considerable revision of the approach to the development and validation of analytical procedures that is currently used in the Eurasian Economic Union (EAEU). A revision is also needed for the processes for evaluating and introducing variations to the analytical procedures described in medicinal product registration dossiers.AIM. This review aimed to analyse the significant changes made to international approaches to the development of analytical procedures, as well as to study the advantages and disadvantages of these approaches for pharmaceutical manufacturers and regulatory agencies in the EAEU.DISCUSSION. This review covers the key provisions and practical aspects of the enhanced approaches to the development of analytical procedures introduced by the ICH Q14 guideline. In particular, the review addresses the concepts of the analytical procedure life cycle (APLC) and the modified analytical quality-by-design (AQbD) approach; the development of the analytical target profile (ATP); analytical quality risk management; planning of the design of experiments (DoE) and the analytical procedure control strategy; and the validation, subsequent verification, transfer, and change management of analytical procedures. Additionally, the review describes the ICH Q2(R2) updates that accompany this new regulatory paradigm.CONCLUSIONS. The above guidelines fill the existing gap in recommendations for the development of analytical procedures. The use of the APLC and AQbD concepts provides both pharmaceutical companies and regulatory authorities with flexible approaches that are applicable to analytical procedures both during the development phase and once they have been implemented. Effective implementation of these international approaches in the Russian pharmaceutical industry and regulatory system requires a broad discussion between pharmaceutical industry professionals and regulatory agency experts, possibly, as part of a pilot project. After that, there will be a necessity to provide training for specialists involved in the development of analytical procedures and to amend the EAEU Rules for Marketing Authorisation and Expert Assessment of Medicinal Products for Human Use.